2008
DOI: 10.1128/jcm.01551-07
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Transmission of and Colonization by Streptococcus pneumoniae and Haemophilus influenzae within a Day Care Center Revealed in a Longitudinal Study

Abstract: Day care centers (DCCs) are unique settings where young children are at increased risk for colonization by pneumococci and Haemophilus influenzae. Although point prevalence studies in DCCs are frequent, only a few longitudinal studies on the dynamics of colonization have been published. We conducted a 1-year longitudinal study with 11 sampling periods on nasopharyngeal carriage of pneumococci and H. influenzae among 47 children who attended a single DCC. All isolates were antibiotyped and genotyped by pulsed-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 27 publications
8
87
0
1
Order By: Relevance
“…One study out of Portugal found 7% of carriage isolates to be NESp, with all NESp strains being resistant to one antibiotic and 89% of them being resistant to multiple. 33 , 45 Another possibility is genetic exchange between NESp and encapsulated strains. The cps locus is considered a hotspot due to abnormally high horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…One study out of Portugal found 7% of carriage isolates to be NESp, with all NESp strains being resistant to one antibiotic and 89% of them being resistant to multiple. 33 , 45 Another possibility is genetic exchange between NESp and encapsulated strains. The cps locus is considered a hotspot due to abnormally high horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Antibioticresistant isolates obtained between 1996 and 2003 were characterized before (19,21,33,37). Isolates obtained in 2006 were partially described (according to their serotypes) before (29), and isolates obtained in 2007 are first described in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Nasopharyngeal sampling, transport, pneumococcal isolation, identification, and preparation of frozen stocks were done as previously described (29,32).…”
Section: Methodsmentioning
confidence: 99%
“…As crianças, por apresentarem elevado índice de colonização, assumem papel importante na disseminação horizontal deste patógeno na comunidade 3 . Pelo uso frequente de antimicrobianos na infância, este grupo de portadores representa um importante reservatório de cepas resistentes 2,4,10,11 .…”
Section: Introductionunclassified